2014
DOI: 10.4037/ajcc2014747
|View full text |Cite|
|
Sign up to set email alerts
|

Feasibility and Acceptability of a Resilience Training Program for Intensive Care Unit Nurses

Abstract: BackgroundThe critical nursing shortage is particularly apparent in specialty areas such as intensive care units (ICUs). Some nurses develop resilient coping strategies and adapt to stressful work experiences, mitigating the development of common maladaptive psychological symptoms. Objectives To determine if a multimodal resilience training program for ICU nurses was feasible to perform and acceptable to the study participants. Methods In a randomized and controlled 12-week intervention study, treatment and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
265
1
16

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(294 citation statements)
references
References 42 publications
8
265
1
16
Order By: Relevance
“…One small, randomized controlled trial of a resilience training program in ICU nurses implemented a multimodal intervention of written exposure therapy, mindfulness-based stress reduction, exercise, and event-triggered cognitive behavioral therapy sessions (15). The results suggested that the intervention was feasible and acceptable.…”
mentioning
confidence: 99%
“…One small, randomized controlled trial of a resilience training program in ICU nurses implemented a multimodal intervention of written exposure therapy, mindfulness-based stress reduction, exercise, and event-triggered cognitive behavioral therapy sessions (15). The results suggested that the intervention was feasible and acceptable.…”
mentioning
confidence: 99%
“…Several studies confirm that the workload is a major factor predisposing to the BS and could negatively influence professional fulfillment. [22][23][24] It is important to emphasize that the aim of this study was not to evaluate the incidence of WRMD and BS, but the findings indicate the presence of factors that can lead to the development of these common diseases in the nursing labor scenario. Therefore, it is essential to analyze the environment and the LSIE work organization, as nursing professionals from these institutions may also be affected by these occupational diseases.…”
Section: -25mentioning
confidence: 99%
“…20 Several authors have reported the presence of musculoskeletal disorders among nursing professionals, showing that physical overload, and consequent illness, is already inherent to this area. [21][22][23][24] Nursing professionals develop their activities on an ongoing basis, which involves physical effort, especially by heavy lifting, awkward positions, repetitive movements, thus predisposing them to the risk of illness caused by work, and reducing job satisfaction.…”
Section: ] (Nt 2; Lsie C)mentioning
confidence: 99%
“…93 Furthermore, ICU nurses' daily encounters with suffering, grief, and death make them prone to the development of psychological disorders such as depression, anxiety, burnout, and posttraumatic stress disorder. 94 Mealer et al 95 state that resilience training may be helpful to mitigate the development of maladaptive psychological symptoms, and they tested the feasibility and acceptability of a multimodal program in a randomized controlled 12-week intervention pilot study. In the intervention arm, 13 nurses followed a 2-day educational workshop, written exposure therapy, mindfulness-based stress reduction techniques, aerobic exercises, and event-triggered counseling sessions.…”
Section: Care For Caregiversmentioning
confidence: 99%
“…despite the promising results of this trial, a sufficiently powered randomized controlled trial is needed to determine the effect of a multimodal resilience program on enhancing psychological outcomes and individual nurses' level of resilience. 95 In the ICU, timely and accurate completion of procedures is vital in ensuring good outcomes for patients. It is, however, also well known that there is a positive correlation between critical care nurses' shift length and the rate of medical errors.…”
Section: Care For Caregiversmentioning
confidence: 99%